2019
DOI: 10.22319/rmcp.v10i3.4609
|View full text |Cite
|
Sign up to set email alerts
|

Key factors influencing the sale of bulls in livestock auctions

Abstract: This research determines which factors most influence the purchase price of bulls in livestock auctions in the State of Rio Grande do Sul, Southern Brazil. Hence, 760 beef bulls sold in eleven different auctions between August and November 2013 were analysed. The data consists of: breed, muscularity (MUSC), frame (FRAME), body condition score (BCS), scrotal circumference (SC) and body weight (BW). Other data such as the animal entry order and the purchase price of the bulls was collected during the auction. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Similarly, there was a strong, positive and signi cant (P<0.01) correlation between BW and BCS change in the age categories of 2-3 years, 4-5 years and overall bulls. This is corroborated by the previous work that con rms that there were strong relationship between BCS and BW change in cattle (Díaz-López et al 2017;Evangelista et al 2019) The regression equation predicting live weight change per body condition change for the two-age group and the entire experimental bulls were presented in Table 7. Accordingly, it means that change of one condition score is equivalent to 22.66, 20.87, 22.65 and 28.66 kg body weight in Arsi, Borana, Harar and HF-crossbred bulls respectively.…”
Section: Resultssupporting
confidence: 82%
“…Similarly, there was a strong, positive and signi cant (P<0.01) correlation between BW and BCS change in the age categories of 2-3 years, 4-5 years and overall bulls. This is corroborated by the previous work that con rms that there were strong relationship between BCS and BW change in cattle (Díaz-López et al 2017;Evangelista et al 2019) The regression equation predicting live weight change per body condition change for the two-age group and the entire experimental bulls were presented in Table 7. Accordingly, it means that change of one condition score is equivalent to 22.66, 20.87, 22.65 and 28.66 kg body weight in Arsi, Borana, Harar and HF-crossbred bulls respectively.…”
Section: Resultssupporting
confidence: 82%
“…This fact is supported by previous research conducted by Dhuyvetter et al (1996) and Jones et al (2008), who found that the price of bulls decreased as sales progressed due to a lack of interest and a smaller pool of buyers. The price reduction that occurred during the auctions can also be explained by the quality of the animal (Evangelista et al, 2019) and buyer behavior. Sellers tend to offer the best quality animals at the beginning of the auction, and buyers are willing to pay more for these animals.…”
Section: Marketing Factorsmentioning
confidence: 99%
“…[41].The regression equation predicting live weight change per body condition change for the two-age group and the entire experimental bulls were presented in Table 7. Accordingly, it means that change of one condition score is equivalent to 22.66, 20.87, 22.65 and 28.66 kg body weight in Arsi, Borana, Harar and HF-crossbred bulls respectively.…”
mentioning
confidence: 99%